Development and Implementation of Students' Scientific Argumentation Skills Test in Acid-Base Chemistry - Parlan, Parlan; Latifah, Umi; Muntholib, Muntholib (Tadris: Jurnal Keguruan dan Ilmu Tarbiyah, 2020)
This study aimed to develop and validate Scientific Argumentation Skills Test (SAST) and investigate the 11th-grade students' performance in scientific argumentation skills on acid-base chemistry. The research design used was research and development, followed by descriptive research. Research and development were carried out to obtain an instrument of SAST, and descriptive research was used to describe students' argumentation skills in acid-base chemistry. Participants in this study were 328 11th-grade students of state high schools in East Java, Indonesia. The research and development of SAST consisted of five steps, namely literature review, items development, expert judgment, pilot project, and finalization of instruments. Expert judgment involved three chemistry education experts, while the pilot project involved 151 students, and the identification of students' scientific argumentation skills involved 177 students. Data about expert assessments, student responses to the pilot project, and student answers to the application of SAST were analyzed descriptively. The SAST produced in the research and development steps consisted of parts A (10 items) and part B (7 items), with Cronbach's alpha reliability coefficients of 0.888 and 0.758. The students' performance in scientific argumentation skills showed that the average score of students' performance to determine the argument's components was 80.53% (excellent category). The average score of students' performance to write an argument was 55.42% (moderate category). The implication of the study that the students' scientific argumentation skills must be explicitly trained in learning.